Adaptation and grain yield of quality protein maize hybrids in Mexican tropical and subtropical regions. - Preciado, Ernesto (2006)
A national quality protein maize program was initiated to develop, identify and release high yield potential quality protein maize hybrids and varieties adapted to different regions. Three-way crosses were predicted, based on 10 quality protein maize inbred lines diallel, which were evaluated at five Mexican locations during 1997. The predicted three-way crosses performance were evaluated at 11 tropical and subtropical Mexican locations during 1999. The superior group of predicted three-way crosses showed a good performance in almost all locations. They were competitive in grain yield with quality protein maize single crosses and normal commercial hybrids. The three-way quality protein maize hybrids with the best adaptation across locations were hybrids which involved tropical and subtropical inbred lines. In tropical regions the highest grain yield (10 t/ha) were obtained at Iguala, Guerrero. In subtropical regions the highest grain yield (16 t/ha) were obtained at Celaya, Guanajuato. The predicted three way hybrids are considered a good alternative for countries with tropical and subtropical climate were the use of single crosses is not common yet, because of seed production problems, with the advantage of quality protein maize character for regions where maize consumption is significant.